The Implications of Using Digital Technologies in the Management of COVID-19: Comparative Study of Japan and South Korea - Sou Hee Yang (JMIR Publications, 2023)
BackgroundTechnology can assist in providing effective infectious disease management, but it can also become a source of social injustice and inequality. To control the rapidly increasing SARS-CoV-2 infections and promote effective vaccine administration, both South Korea and Japan have been using several technology-based systems and mobile apps. However, their different approaches to technology use have yielded contrasting social implications. ObjectiveThrough comparative studies of the use of digital technologies for pandemic management and its social implications in Japan and South Korea, this study aimed to discuss whether the active and optimal use of technology for pandemic management can occur without subverting or compromising important social values, such as privacy and equality. MethodsThis study compared the social implications of Japan's and South Korea's contrasting approaches to technology implementation for COVID-19 pandemic management in early 2022. ResultsDigital technologies have been actively and comprehensively used in South Korea, enabling effective COVID-19 management, but have raised serious concerns about privacy and social equality. In Japan, technologies have been more carefully implemented, thereby not causing similar social concerns, but their effectiveness in supporting COVID-19 regulations has been criticized. ConclusionsPotential social implications such as equality concerns, the balance between public interest and individual rights, and legal implications must be carefully assessed in conjunction with effective and optimal infectious disease control to achieve sustainable use of digital health technologies for infectious disease management in the future.